2013
DOI: 10.6061/clinics/2013(09)11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperbaric oxygen therapy combined with autologous platelet concentrate applied in rabbit fibula fraction healing

Abstract: OBJECTIVES:The purpose is to study the effects of hyperbaric oxygen therapy and autologous platelet concentrates in healing the fibula bone of rabbits after induced fractures.METHODS:A total of 128 male New Zealand albino rabbits, between 6–8 months old, were subjected to a total osteotomy of the proximal portion of the right fibula. After surgery, the animals were divided into four groups (n = 32 each): control group, in which animals were subjected to osteotomy; autologous platelet concentrate group, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
1
4
0
3
Order By: Relevance
“…Neves et al compared a control group to combined and separate PRP and HBO in the treatment of osteomyelitis in his experimental study. The combination therapy was reported as successful in terms of the activity of osteoblasts, osteocytes, and collagen [24]. In the present study, we found that separate treatments were useful for collagen fiber regeneration and dermal angiogenesis, but combination therapy was more successful for wound healing.…”
Section: Discussionsupporting
confidence: 53%
“…Neves et al compared a control group to combined and separate PRP and HBO in the treatment of osteomyelitis in his experimental study. The combination therapy was reported as successful in terms of the activity of osteoblasts, osteocytes, and collagen [24]. In the present study, we found that separate treatments were useful for collagen fiber regeneration and dermal angiogenesis, but combination therapy was more successful for wound healing.…”
Section: Discussionsupporting
confidence: 53%
“…Additionally, a significant bone formation was observed when PRP was used with biphasic CaP or PGA containing BMP-2 [ 64 , 67 ]. A different application was proposed by Paulo et al, which treated rabbit fibula fracture with PRP and daily hyperbaric oxygen therapy sessions, with promising results [ 75 ]. However, several studies found opposite outcomes [ 76 ] compared to those just quoted, in particular, when PRP was used in association with ceramic [ 77 80 ], metallic [ 81 ], or composite materials [ 82 ].…”
Section: The Role Of Prp In the Regeneration Of Bonementioning
confidence: 99%
“…Another set of positive results with the combination of PRP and HBO was achieved by Neves et al, [35] who showed an increased healing process in the bones of rabbits with fibula defects via the combined application of HBO and autologous platelet concentrates (APCs). Neves et al [35] showed an enhanced percentage of collagen and decreased lesion thickness with the combined use of HBO and APC as compared to the control group, APC group, and HBO group.…”
Section: Discussionmentioning
confidence: 99%